Low-Cost Multifunctional Assistive Device for Visually Impaired Individuals - Richard Kral; Patrik Jacko; Tibor Vince (IEEE Access)
Visually impaired individuals face challenges in mobility, object recognition, and text reading. Existing assistive tools provide partial solutions but lack full integration. This paper presents a low-cost, multifunctional assistive device in the form of wearable glasses, integrating real-time text recognition, obstacle detection, and remote assistance. Built around a Raspberry Pi Zero 2W, the system features an Arducam IMX519 autofocus camera and a tactile button interface for user-friendly control. Real-time audio feedback enhances situational awareness, promoting greater independence. The device was tested at the Rehabilitation Center for the Visually Impaired in Levoča. Performance evaluations confirm high text recognition accuracy and improved navigation support. A comparative analysis highlights its affordability and functionality over commercial alternatives. While effective, the device requires processing speed optimization and hardware miniaturization. Future improvements will explore haptic feedback and AI-driven scene analysis to enhance usability. This research contributes to affordable and inclusive assistive technology, improving accessibility for visually impaired individuals.